2009
DOI: 10.1080/13102818.2009.10818358
|View full text |Cite
|
Sign up to set email alerts
|

The Only Good Snake is a Dead Snake: Secondary School Students' Attitudes Toward Snakes

Abstract: This cross-age study investigates the secondary school students' attitudes toward snake. Responses were elicited from a convenience sample of students (9 th , 10 th , 11 th , and 12 th grade, n=188). A Likert-type "Shark Attitude Inventory" developed by Thompson and Mintzes (2002), adapted for snakes and with name of "Snake Attitude Scale" (SS) was used for data collection. The attitude scale, on the basis of "nine attitudinal typologies toward wildlife" defined by Stephen R. Kellert, generated subscale scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 6 publications
3
15
0
3
Order By: Relevance
“…Therefore, our results suggest the need for more theoretical investments in this conceptual understanding in formal educational processes, especially in the rural context where the aforementioned understanding is more critical. In short, efficiency in conceptual understanding of biodiversity and its conservation presupposes a rethinking of the curriculum from a more contextual, systemic, and interdisciplinary perspective [6,9,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, our results suggest the need for more theoretical investments in this conceptual understanding in formal educational processes, especially in the rural context where the aforementioned understanding is more critical. In short, efficiency in conceptual understanding of biodiversity and its conservation presupposes a rethinking of the curriculum from a more contextual, systemic, and interdisciplinary perspective [6,9,18].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies involving relationships between students and animals highlight some issues related to the aforementioned perspectives, including school learning about fauna that tends to be dissociated from real situations, contributing to conceptual misunderstanding and limited knowledge [6]; science and biology curricula should include some content related to local biodiversity, with more emphasis on endangered species, and not be limited to exotic animals [8]; and formal education, in general, devotes little time to the study of biodiversity, which occurs almost exclusively by means of information through decontextualized schemes and images [7]. Therefore, the search for a conceptual understanding of biodiversity and its conservation needs a curriculum that is based on a more contextual, systematic, and interdisciplinary perspective [9].…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the diversity of living beings and, above all, the recognition of the importance of each species for ecological sustainability is a fundamental condition for the development of human behaviors and attitudes compatible with the conservation of nature [1]. Knowledge about biodiversity, made explicit by means of the naming of species, constitutes an indication of connectivity between humans and their immediate environment [2, 3] and contributes to the development of subsequent learning [4].…”
Section: Introductionmentioning
confidence: 99%
“…These interactions had repercussions in determining cultural patterns of affinity or aversion, depending on the vertebrate and its relation with people in each context [2, 1517], thereby guiding behaviors and consequent attitudes towards animal conservation [18]. In this context, studies have recognized a tendency for greater affinity for large vertebrates that are showy in appearance, utilitarian, and charismatic [1, 3, 7, 8], including representatives of mammals, birds, and fish [2, 15], and, inversely, aversion to less showy, “unpleasant-looking” animals, seen as being useless or harmful to humans, including mainly representatives of amphibians and reptiles [15, 1921]. This tendency generally leads to conservation projects that emphasize “lovable” species, especially mammals and birds, thus neglecting other less charismatic animals [10, 22], such as representatives of reptiles and amphibians [20].…”
Section: Introductionmentioning
confidence: 99%
“…Snakes are an ambivalent stimulus perceived as a source of actual or evolutionary fixed danger that attracts specialized attention and triggers fear. Together with a negative picture caused by the media, this may result in negative attitudes toward snakes in both adults (Pandey et al, 2016 ) and children (Yorek, 2009 ; Ballouard et al, 2013 ), including snake killing (Pandey et al, 2016 ). It has been demonstrated that more negative attitudes toward snakes may be associated with a higher risk of snakebite in the specific region.…”
Section: Introductionmentioning
confidence: 99%